2014
DOI: 10.1002/cyto.a.22462
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry as a rapid and reliable method to quantify sperm viability in the honeybee Apis mellifera

Abstract: An important measure of male quality is sperm viability; i.e., the percentage of live sperm within an ejaculate, as this provides an accurate measure of the number of sperm potentially available for egg fertilization. Sperm viability is often determined by fluorescence microscopy using dyes that differentially stain viable and nonviable sperm, but the technique has a number of limitations. Here, a flow cytometry (FCM) method was developed, which allows the rapid determination of honeybee sperm viability, facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
(67 reference statements)
1
24
0
Order By: Relevance
“…Up to now, several authors have reported data on spermatozoa viability in honeybee drones representing great variation, measured by fluorescent staining technique combined with microscopy (Collins and Donoghue 1999;Collins and Pettis 2001;Collins 2003Collins , 2004Lodesani et al 2004;Burley et al 2008;Gençer and Kahya 2011a;Bieńkowska et al 2011;Czekoňska et al 2013a, b;Stürup et al 2013) or with flow cytometry (Rzymski et al 2012;Tofilski et al 2012;Paynter et al 2014). Our finding that the spermatozoa viability in seminal vesicles is higher than that in ejaculate collected into the syringe tip is in agreement with the finding of Collins (2004).…”
Section: Discussionsupporting
confidence: 89%
“…Up to now, several authors have reported data on spermatozoa viability in honeybee drones representing great variation, measured by fluorescent staining technique combined with microscopy (Collins and Donoghue 1999;Collins and Pettis 2001;Collins 2003Collins , 2004Lodesani et al 2004;Burley et al 2008;Gençer and Kahya 2011a;Bieńkowska et al 2011;Czekoňska et al 2013a, b;Stürup et al 2013) or with flow cytometry (Rzymski et al 2012;Tofilski et al 2012;Paynter et al 2014). Our finding that the spermatozoa viability in seminal vesicles is higher than that in ejaculate collected into the syringe tip is in agreement with the finding of Collins (2004).…”
Section: Discussionsupporting
confidence: 89%
“…Although less accurate than flow cytometry methods, fluorescence-based methods have been widely used and they are well accepted as standard methods (Thomas & Simmons., 2007;den Boer et al, 2008den Boer et al, , 2010Cobey et al, 2013). Moreover, sperm viability obtained with fluorescence microscopy and flow cytometry has been found indistinguishable in some cases (Paynter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is also commonly used in other organisms to study various aspects of their reproductive biology (Garner et al, 1994;Ball et al, 2001;Paulenz et al, 2002). Recent advances in the use of flow cytometry to assess sperm traits in social insects allowed significant improvements, decreasing processing times and increasing accuracy (Cornault & Aron, 2008;Paynter et al, 2014). However, flow cytometry equipment is not common across the tropics (where stingless bees occur), and the costs involved in their use and maintenance are substantially higher than those involving fluorescence-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of mitochondrial membrane potential (MMP) is important for evaluating the function of mitochondria, which are particularly vital for the production of energy during sperm movement. The use of flow cytometry, rather than fluorescence microscopy, facilitates high-throughput analysis and enables the quantification of thousands of sperm cells per sample and between the implementation of blind counting and randomization (Holman 2009;Rzymski et al 2012;Paynter et al 2014).…”
Section: Introductionmentioning
confidence: 99%